Microclimate and the vertical stratification of potential bridge vectors of mosquito‑borne viruses captured by nets and ovitraps in a central Amazonian forest bordering Manaus, Brazil - Scarpassa, Vera Margarete; Chaves, Bárbara Aparecida; Assunção, Flamarion Prado; Andes Júnior, José Tenaçol; Costa, Edson Rodrigues; Pedrosa, Igor; Andrade, Eloane; Mendonça, Claudia; Hernandez Acosta, Eduardo; Fé, Nelson Ferreira; Valério, Danielle; Hendy, Adam (Scientific Reports, 2021)
In the Americas, some mosquito-borne viruses such as Zika, chikungunya, and dengue circulate among humans in urban transmission cycles, while others, including yellow fever and Mayaro, circulate among monkeys in sylvatic cycles. The intersection of humans and wildlife at forest edges creates risk for zoonotic virus exchange. We built a scaffold tower at the edge of a treefall gap in rainforest bordering Manaus, Brazil, to identify vectors that may bridge transmission between humans and monkeys. We vertically sampled diurnally active, anthropophilic mosquitoes using handheld nets at 0, 5, and 9 m and container-breeding mosquitoes in ovitraps at 0, 5, 10, and 15 m. Haemagogus janthinomys and Psorophora amazonica were present in high relative abundance in nets at each height sampled, while anthropophilic species were uncommon in ovitraps. Hg. janthinomys was more abundant at elevated heights than at ground level, while Ps. amazonica abundance was not significantly stratified across heights. The presence of each species increased with increasing 7-day rainfall lagged at 1 week, and at 1 and 4 weeks prior to collection, respectively. In addition, Hg. janthinomys was most frequently collected at 29.9 °C, irrespective of height. These data provide insight into the potential role of each species as bridge vectors. © 2021, The Author(s).